Metodologias não convencionais na extração de compostos bioativos de casca de bergamota - Soquetta, Marcela Bromberger (2019)
Citrus fruits, produced in large quantities in Rio Grande do Sul, have been highlighted by the high content of bioactive compounds they present. These components can be extracted from the residues generated in the processing of these fruits, allowing the use of these by-products, as well as the use of extracts for nutritional enrichment, protection and/or pigmentation in the food industry. Conventional extraction is based on heating and/or stirring the raw material with organic solvents. Unconventional extractions are considered promising and can reduce or eliminate the use of organic solvents and minimize compound degradation, time and energy expenditure. Ultrasound assisted extraction (UAE) and supercritical fluid extraction (SFE) have been highlighting in recent years. An alternative for reducing the use of organic solvents may be the use of electrolyzed water (EW). Therefore, the objective of this work was to extract bioactive compounds from bergamot peel using electrolyzed water as a solvent for ultrasonic extraction and co-solvent for supercritical fluid (CO2) extraction. First, the physicochemical and microbiological characterization, the determination of bioactive compounds (total phenolic and total flavonoids) and antioxidant activity (DPPH, superoxide radical, hydroxyl and FRAP) of the varieties Citrus deliciosa, Citrus reticulata and Citrus reticulata Blanco were compared using 80 % ethanol and the three types of EW, acidic (AEW), basic (BEW) and slightly acidic (SAEW), as extractor solutions were performed. Subsequently, the extraction methods with ultrasound, supercritical fluid and their combination were tested using electrolyzed water as solvent and as co-solvent (SFE), respectively. According to the results, the Citrus reticulata variety presented higher values of total phenolics (3681.31 mgGAE (100g) -1 ) and total flavonoids (571.56 mgEQ (100g) -1 ) compared to the other varieties. The three types of electrolyzed water presented higher extraction capacity of bioactive compounds than 80 % ethanol, the Citrus reticulata variety with BEW extracted 25 % more from total phenolics and 50 % from flavonoids, while AEW was 14 % higher antioxidant activity (FRAP). The UAE showed 87.5 % reduction in process time compared to conventional extraction. Among the responses of ultrasonic extractions combined with electrolyzed water, the highest extraction of phenolics (4324.32 mgGAE (100) -1 ) and FRAP (663.69 µmolTEAC (100g) -1 ) was using UAE+SAEW, while for flavonoids (691, 76 mgEQ (100g) -1 ) was UAE+AEW. At SFE-CO2 the BEW was the best co-solvent for all analyzes. The results of combined extraction, ultrasound and supercritical CO2 showed no significant difference compared to supercritical CO2 extraction only. For phenolics, the best result (5344.59 mgGAE (100g) -1 ) was obtained at 40 °C, extract: co-solvent ratio 1:40 (w/v) and 10 MPa pressure for flavonoids (1271.53 mgEQ (100g) ) was at 80 °C 1:20 (w/v) and 10 MPa and for FRAP (854.85 µmolTEAC (100g) -1 ) it was at 80 ° C 1:40 (w/v) and 10 MPa. Unconventional extractions were efficient in reducing the time and elimination of organic solvents in the extraction of bergamot peel bioactive compounds. Extraction with supercritical fluid (CO2) using basic electrolyzed water as co- solvent is the best method of extracting bioactive compounds from Citrus reticulata.